Resilience in Local Housing Policy? Liberal or Restrictive Policy Stances Among Swedish Municipalities Following the Great Migration in the Summer of 2015 - Holmqvist, Emma; Jutvik, Kristoffer; Lidén, Gustav (Frontiers in Political Science, 2022)
The dramatic event that the European migrant crisis entailed changed the migration policies of various countries. Substantial amendments were hastily made in a policy field in which already tense state-local relations struggled to manage coordination, responsibilities, and funding. Sweden, recognized as a final host country of the massive flows of refugees and asylum-seekers, was no exception. In Sweden, autonomy in terms of local refugee reception was circumvented in 2016. Municipalities’ remaining discretion is above all concentrated to one of the most crucial spheres of refugee reception: the outline of local housing policies. We argue that housing, besides its key role in the process of settlement and inclusion, may be perceived as a tool of resilience that local governments may use to maintain far-reaching influence over the settlement of migrants with a refugee background by selecting restrictive or generous policy options. In this paper, we conduct a theoretically grounded analysis of local housing policy for refugees among Swedish municipalities. To capture the intrinsic dynamic, we propose a generic typology applying the dimension of either a liberal or a restrictive housing policy and relate it to theoretical notions of refugee policy as characterized by either a rights-based or a more restrictive approach. Our findings show that local governments in Sweden pursue a wide array of policy stances that appear to be correlated with factors originating from prior experiences of refugee reception, conditions in the labor and housing markets, and political circumstances. Based on this, we argue that local housing policy has offered municipalities a tool to exert a form of intentional, or unintentional, migration control despite national efforts to impose a more just system of refugee reception. In terms of ensuring their own interests, Swedish municipalities have stretched the current legislation as far as possible and thereby managed the pressure otherwise implied by new legislation. Protecting borders can be done in the name of resilience to safeguard the carrying capacity of local societies. The various outcomes of housing policy that we reveal imply that local governments perceive their capacity and utility of maintaining long-term settlement for refugees differently.